A Case of Surgical Site Infection Caused by Mycobacterium fortuitum, following Herniorrhaphy - Madhusudhan, NS (J Clin Diagn Res, 2016)
Rapidly Growing Mycobacteria (RGM) are opportunistic pathogens found in the environment. Mycobacterium fortuitum, M. chelonae and M.abscessus are the important human pathogens of this group. They cause wound infections, disseminated cutaneous disease, pulmonary infection in patients with cystic fibrosis or bronchiectasis, bone and joint infections and keratitis. Infections due to these Non-Tuberculous Mycobacteria (NTM) are increasingly reported. Post laparoscopic wound infections, mesh site infections and other surgical site infections due to M. fortuitum and M. chelonae have been reported. Usually wound infections due to atypical mycobacteria have delayed onset and do not respond to conventional antibiotics. Identification of RGM can be done by a set of cumbersome biochemical tests, High Performance Liquid Chromatography (HPLC), molecular methods using DNA probes or by Polymerase Chain Reaction (PCR). We here report a case of post-herniorrhaphy wound infection due to M. fortuitum which was identified by molecular method (HAIN mycobacterial species system). This case report underscores the importance of examining Ziehl-Neelsen (ZN) stain of all exudates with sterile culture on day one for non fastidious bacteria. Timely identification can lead to prompt therapy of patients preventing further complications.